The tadpole of Ramanella palmata (Anura: Microhylidae), a frog endemic to Sri Lanka - Ukuwela, K. D. B.; Silva, E. I. L.; Athukorala, N. P. (Zootaxa, 2010)
Of the 107 species of amphibians known from Sri Lanka (Megaskumbura et al. 2009), the family Microhylidae is represented by 10 species (Pethiyagoda et al. 2006). The genus Ramanella Rao and Ramanna, 1925 is represented by four species in Sri Lanka (Pethyagoda et al. 2006). Except for R. variegata (Stoliczka, 1872), which is also found in neighboring India, the other three species are endemic to Sri Lanka. Larval stages and the breeding ethology of R. obscura (Guenther, 1864) and R. nagaoi Manamendraarachchi and Pethiyagoda, 2001 are well known (Morgan-Davis 1953; Meegaskumbura 2001; Manamendraarachchi & Pethyagoda 2001). Kirtisinghe (1958) briefly outlined the general morphology of the R. palmata tadpoles. Here we re-describe tadpoles of R. palmata highlighting some important characters that were initially not described by Kirtisinghe (1958), provide standard morphometric measurements of the tadpoles and also a photograph.